Lower bone mineral density in older female endurance skiers – a cross-sectional, observational study - Gulsvik, Anne Kristine; Myrstad, Marius; Landgraff, Ida Wilson; Emaus, Nina; Ranhoff, Anette Hylen (European Review of Aging and Physical Activity, 2018)
Source at https://doi.org/10.1186/s11556-018-0202-1 . Background : Physical activity (PA) is generally beneficial for bone health, but the effect of high levels of PA over many years, in older women, is unknown. Methods : T-score from Dual-energy X-ray absorptiometry (DXA), and self-reported baseline characteristics were recorded for 24 female, cross-country-skiing-competitors, aged 68–76 years, from the Birkebeiner Ageing Study. Data from 647 women in the same age range from the Tromso-6 population study, with recorded DXA findings, were used for comparison. Results : The athletes reported a median(range) of 9(1–34) participations in the 54 km, yearly ski-race, indicating long-term PA. They also reported more moderate and high levels of PA than women in the general population (52% vs. 12 and 30% vs. 0%, respectively). The athletes had lower body mass index (BMI) than the controls (mean BMI 21.7 vs 26.9 kg/m2, p < 0.001). As many as 22/24(92%) of the athletes and 477/647(74%) of the controls had a low bone mineral density (BMD) (T-score < − 1), p 0.048, Pearson chi square test. Odds ratio (OR) of low BMD was 3.9 in athletes vs. controls (p 0.048, logistic regression), but adjusting for BMI largely diminished the effect estimate, which was no longer statistically significant (aOR 1.81, p 0.432). The proportion of self-reported fractures was the same in the two groups. Conclusions : This pilot study suggests that long-term, high levels of PA are associated with low bone mineral density in older women, and the finding might be due to differences in BMI. Despite the lower bone mineral density the athletes did not report more fractures.